Effect of axial stiffness of NSM FRP reinforcement and concrete cover confinement on flexural behaviour of strengthened RC beams: Experimental and numerical study. (15th October 2018) - Sharaky, I.A.; Baena, M.; Barris, C.; Sallam, H.E.M.; Torres, L.
Highlights: The strengthened beams without confinement suffered from concrete cover failure. The used confinement methods enhanced the performance of the NSM technique. A critical value of the stiffness ratio for NSM system efficiency was identified. Abstract: An experimental and numerical study was performed to study the effectiveness of axial stiffness and of the type of confinement of near-surface mounted (NSM) fibre reinforced polymer (FRP) reinforcement on the strengthened beam bearing capacities and failure modes. To improve the performance in front of concrete cover separation and enhance bond strength, the use of mechanical interlocking with shear connectors (concrete cover confinement) or transverse wrapping was also investigated. The experimental results showed that confinement significantly enhanced the load carrying capacity of the RC beams with small increase in their steel reinforcement yielding load. The ultimate load of the strengthened beams without concrete cover confinement ranged between 150% and 170% of the ultimate load of the control beam. By applying mechanical interlocking with shear connectors or transverse wrapping, the load carrying capacity was increased by up to 23.3% for strengthened beams and by 33% for the ultimate load of conventional strengthened beams. The results indicated that the yield load ratio of the strengthened beams (with respect to the control beams) was proportional to the axial stiffness ratio of NSM FRP reinforcement. It was found that the failure of the strengthened beams became concrete cover separation when the axial stiffness ratio reached a critical value, and subsequently the ultimate load of strengthened beams was not affected by increasing axial stiffness ratio beyond this value. This critical value of stiffness ratio was experimentally found to be at about 1.25. The numerical results also showed excellent agreement with the experimental ones in terms of load–deflection behaviour and maximum load capacity.